Influence of Peer Approval Seeking, Socio-Economic Status and Locus of Control on Academic Self-Handicapping Behaviour of Undergraduates in Oyo State, Nigeria (British Journal of Multidisciplinary and Advanced Studies, 2023)
The study investigated the influence of peer approval seeking, socio-economic status and locus of control on academic self-handicapping behaviour of undergraduates in Oyo State Descriptive survey research design was adopted in the study and five universities were selected based on distribution of universities’ ownership. Three faculties were purposively selected with a study population of 3,415. Random sampling procedure was employed using a sampling percentage of 10% to give a sample size of 341. Questionnaire was the instrument used in the collection of data and data were analysed using simple percentage, correlation, independent sample t test and regression. Results revealed that the level of academic self-handicapping behaviour of undergraduates was moderate 2.27). There was significant positive relationship between peer approval seeking and academic self-handicapping behaviour (r = 0.314, p